Morphology, Conductivity and Microwave Absorption Behavior of Polyaniline Nanocomposites after Chemical Treatment. Issue 7 (September 2017) - Mokhtar, Nurrafiqah; Chye, Desmond Ang Teck; Phang, Sook Wai
In this study, the hexanoic acid (HA) doped Polyaniline (PAni) nanocomposites which comprise aniline (Ani) as a monomer, titanium dioxide (TiO2 ) as a dielectric material and fullerene (C60 ) as a carbonaceous material with and without treated with different types of sulfonic groups: dioctyl sodium sulfosuccinate (AOT), sodium dodecylbenzene sulfonicate (DBSA) and camphorsulfonic acid (CSA) were synthesized through the template-free method. The fourier transform infrared (FTIR), ultraviolet-visible (UV-vis), x-ray diffraction (XRD) and thermal gravimetric analysis (TGA) characterization of PAni nanocomposites validated the functional groups, conducting behavior, existing of an inorganic material and thermal stability of PAni nanocomposites, respectively. Besides, an increment of electrical conductivities of the PAni nanocomposites from 3.655 × 10 −2 S/cm (without chemical treatment) to 5.433 × 10 −2 – 1.708 × 10 −1 S/cm (after chemical treatment) was obtained by the four-point probe method. This increment can be explained by the formation of nanorods/nanotubes via field emission scanning electron microscope (FESEM). Based on the data obtained from the microwave vector network analyzer (MVNA), the PAni/HA/TiO2 /C60 nanocomposites (treated with CSA) revealed a narrow and sharp reflection loss (RL) peak with high absorption (−61.3 dB) due to its highest conductivity, dielectric permittivity and heterogeneity which eventually enhanced the microwave absorption properties, while those without chemical treatment showed a broad RL peak with poor absorption (−37.2 dB). Based on the researchers' knowledge, the PAni/HA/TiO2 /C60 nanocomposites with a chemical treatment that shows a good absorption is the first being reported here.